Apoyo emocional y psicológico del personal de enfermería y su relación con los niveles de ansiedad en los pacientes pre-quirúrgicos del Hospital Martín Icaza de Babahoyo. - Macias Parraga, Marcia Yohanna (2018)
The emotional and psychological support in the pre-surgical patient is one of the first steps of the nursing care process, being necessary to identify those signs and symptoms of anxiety, the research project will allow us to establish the relationship between the emotional and psychological support of the nursing staff, with the levels of anxiety in the pre-surgical patients of the Martin Icaza Hospital in Babahoyo. The descriptive method was used, analyzing the reality of the situation to raise its relevance. The investigation was developed in the period May to October 2018. Two surveys were applied to patients (n = 52); the first to assess the level of anxiety and the second to measure the emotional support of the nursing staff, responding to the objectives of the research. More than half of the pre-surgical patients did not receive emotional and psychological support from the nursing staff (n = 27, 52%). Regarding the ability to tune the feelings and emotions as a priority of the pre-surgical patient, it was found that although the nursing professional complies with the necessary care procedures, it does not reflect any concern regarding knowing how to feels emotionally with 94%, this being an important aspect in the pre-surgical stage It was evidenced that the nursing professional does not provide emotional and psychological support to the patient in the pre-surgical stage, presenting a certain level of anxiety valued with the Hamilton scale, they were: mild (16%) and moderate (32%).